The theology of the idol fabrication passages in second Isaiah - Rudman, Dominic (Old Testament essays, 1999)
How do the idol fabrication passages of Second Isaiah function within the work as a whole? This article argues that they establish a comparison not between God and idol, but between God and idol fabricator, who challenges Yahweh by claiming to appropriate divine creative knowledge. This reading of the idol passages is supported by contextual evidence and Akkadian texts dealing with idol fabrication. This in turn suggests that the idol fabricators serve as representatives of the nations in general: as the sole creator of life, only Yahweh can create a new Israel. Dependence on human agents for redemption is implicitly ruled out in these texts.